The geometry of coronary arteries: intravascular ultrasound (in vivo) - Pidvalna, U.Ye. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. The dynamic development of endovascular interventional cardiac procedures contributes to the study of the cardiovascular system in vivo. The intravital evaluation of the coronary bed of the heart can be conducted with the help of intravascular ultrasound, the advantage of which for morphologists is the ability to assess the anatomy and geometry of the coronary arteries from the lumenal surface of the vessel. Objective. To measure the minimum diameter, mean diameter, maximum diameter, and areas of the right and left coronary ostia in women using intravascular ultrasound; to assess the interdependence with age and anthropometric indicators. Methods. The research materials included intravascular ultrasound images, mathematical and statistical calculations. Results. Coronary arteries’ parameters were studied by the IVUS method in 12 women whose mean age was 61.67±10.44 years. On average, the area of the coronary artery in women was 17.16±2.80 mm2 , the average diameter 4.47±0.36 mm, the minimum diameter 4.07±0.45 mm, and the maximum diameter 4.87±0.37 mm. The parameters of the right coronary artery were bigger than those of the left coronary artery, with the most significant difference in the area indicator – by 18.88% (p=0.21). The study of correlation relationships, conducted among all women, did not prove the existence of any significant associations between vascular parameters and age-anthropometric data (p>0.05). Analysis of the combined association of several factors indicated the influence of height and body weight on the coronary arteries’ parameters. The most revealing was the direct interdependence of the value of the minimum diameter of the coronary ostia with mass and height. Conclusion. The minimum diameter, mean diameter, maximum diameter, and areas of the right coronary artery ostium slightly exceeded those of the left coronary artery. Analysis of the combined relationship of several factors established the interdependencies that were not revealed in the study of correlational relationships.